2010
DOI: 10.1002/jca.20271
|View full text |Cite
|
Sign up to set email alerts
|

Plasma extraction rate and collection efficiency during therapeutic plasma exchange with Spectra Optia in comparison with Haemonetics MCS+

Abstract: For therapeutic plasma exchange (TPE), continuous and intermittent flow separators are known to be efficient. This study was undertaken to compare the performances of the Spectra Optia, a continuous flow centrifugal apheresis system recently developed by CaridianBCT, with the Haemonetics Multicomponents System (MCS)+ apheresis system based on intermittent flow centrifugation. The primary objective of the study was to compare the time required to exchange one total plasma volume with both separators. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 14 publications
5
28
3
Order By: Relevance
“…For instance the mean PRE obtained after CSP devices in previous studies ranged from 69% to 79% [4,9,10] and the mean PRE observed after CSP in our study (76%) was in accordance with these results. The mean PRE observed after SPO in our study (79%) was lower than the mean PRE observed in previous studies (84-87%), which could be explained by the higher average blood flow rate in our study and the higher PVs processed in these studies [4,5]. Secondary outcomes as the amounts of ACD-A consumed apheresis duration platelets losses in the waste bags and consequences on the patients' blood were compared in the SPO and CSP sessions.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…For instance the mean PRE obtained after CSP devices in previous studies ranged from 69% to 79% [4,9,10] and the mean PRE observed after CSP in our study (76%) was in accordance with these results. The mean PRE observed after SPO in our study (79%) was lower than the mean PRE observed in previous studies (84-87%), which could be explained by the higher average blood flow rate in our study and the higher PVs processed in these studies [4,5]. Secondary outcomes as the amounts of ACD-A consumed apheresis duration platelets losses in the waste bags and consequences on the patients' blood were compared in the SPO and CSP sessions.…”
Section: Discussioncontrasting
confidence: 79%
“…This study demonstrated that the performances of the SPO improved compared to the performances of CSP and showed no occurrence of significant adverse events [4]. Another group compared the efficiency of the SPO to the efficiency of the MCS+ and showed that the time required to exchange one total plasma volume was shorter when using the SPO and that the performances obtained with the SPO characteristics (mainly analysed using the plasma extraction rate) improved compared to performances obtained with the MCS+ [5].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The Optia is also designed to achieve high plasma extraction rates even at low inlet blood flows and peripheral venous access. 17 To prevent clotting, especially in the case of IA with low inlet blood flow, mixed anticoagulation with heparin is helpful. In 1999, Braun and Risler described anticoagulation for IA.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively, therapeutic plasma exchange (TPE) was performed with the Spectra OPTIA ® apheresis system, to prevent thyroid storm and potential cardiac complications. The Spectra OPTIA device performs a continuous separation through centrifugation and plasma exchange, resulting in high plasma exchange efficiency (80%) [7] . TPE was performed daily and 1-1.5 plasma volumes were exchanged during every procedure.…”
Section: Case Reportmentioning
confidence: 99%